Responses evoked by electrical stimulation of the brainstem reticular formation in the jaw-opening and hypoglossal motor nerves of an arterially perfused rat preparation. (1st November 2020) - Ofuji, Takuo; Nakayama, Kiyomi; Nakamura, Shiro; Mochizuki, Ayako; Dantsuji, Masanori; Ishiguro, Mitsunori; Yamamoto, Matsuo; Inoue, Tomio
Highlights: Stimulation of the extensive brainstem evokes motor activity in orofacial nerve. Mean latency is shorter in the mylohyoid nerve than the hypoglossal nerve. Latency histogram of the hypoglossal nerve responses was separated by 4.0 ms. Sites eliciting short-latency response are different for the two motor nerves. Abstract: The interneuronal system in the brainstem reticular formation plays an important role in elaborate muscle coordination during various orofacial motor behaviors. In this study, we examined the distribution in the brainstem reticular formation of the sites that induce monosynaptic motor activity in the mylohyoid (jaw-opening) and hypoglossal nerves using an arterially perfused rat preparation. Electrical stimulation applied to 286 and 247 of the 309 sites in the brainstem evoked neural activity in the mylohyoid and hypoglossal nerves, respectively. The mean latency of the first component in the mylohyoid nerve response was significantly shorter than that in the hypoglossal nerve response. Moreover, the latency histogram of the first component in the hypoglossal nerve responses was bimodal, which was separated by 4.0 ms. The sites that induced short-latency (<4.0 ms) motor activity in the mylohyoid nerve and the hypoglossal nerve were frequently distributed in the rostral portion and the caudal portion of the brainstem reticular formation, respectively. Such difference in distributions of short-latency sites for mylohyoid and hypoglossal nerve responses likely corresponds to the distribution of excitatory premotor neurons targeting mylohyoid and hypoglossal motoneurons.